(3oZQQ GdNUGFU GdhGVMI hoYQQ GdfbGFU GdaGVMIs - (3eMeO Hf EHQGgje Hf jMji Hf Ydj GdCfUGQj GdcJHj, LeGd GdOjf, GdeYQha H` GdhWhGW,J (B718 (3g` s
(3ChdgG (B:s
(3hHYO aEfj deG QCjJ JZGjQ eYGfj GdCNdGb, OGdkG Ydi JHGjf eHGfj GdCYQGb s
(3BNQgG (B:s
(3hPdc eG dG jLOhf Je GdLRA GdChd, hjdjg GdLRA GdKGfj GdPj Chdg HGH GdSNGA, hajg KdGKI aUhd s
(3fSNI KGfjIs
(3JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B297 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B222 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B143s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B68 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1201s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs